Signaling of the Purinergic System in the Joint - Corciulo, Carmen; Cronstein, Bruce N. (Frontiers in Pharmacology, 2020)
The joint is a complex anatomical structure consisting of different tissues, each with a particular feature, playing together to give mobility and stability at the body. All the joints have a similar composition including cartilage for reducing the friction of the movement and protect the underlying bone, a synovial membrane that produces synovial fluid to lubricate the joint, ligaments to limit joint movement and tendons for the interaction with muscles. Direct or indirect damage of one or more of the tissues forming the joint is the foundation of different pathological conditions. Many molecular mechanisms are involved in maintaining the joint homeostasis as well as in triggering a pathological condition. The molecular pathway activated by the purinergic system is one of them. The purinergic signaling defines a group of receptors and intermembrane channels activated by adenosine, adenosine diphosphate and adenosine 5’-triphosphate. It has been largely described as a modulator of many physiological and pathological conditions including rheumatic diseases. Here we will give an overview of the purinergic system in the joint describing its expression and function in the synovium, cartilage, ligament, tendon and bone with a therapeutic perspective.